(untitled) (International Journal of Ayurveda and Pharma Research, 2019)
ABSTRACT: Rasa Shastra is the pharmaceutical branch of Ayurveda. As like any other medical system, success of Ayurvedic treatment also depends upon quality of medicine prescribed to the patient. The integral part of Rasa Shastra lies in the successful pharmaceutical process. Bhasma are the potent Ayurvedic preparations prepared by metals and minerals. These Bhasma possess wide range of therapeutic efficacy and are considered superior because of their qualities like small dose, quick action, palatability and longer shelf life. Yashada bhasma is important formulation mentioned in Rasa shastra texts obtained from the incineration of Raw Yashada. The pharmaceutical procedures adopted in this study are Shodhana, Jarana, Marana. The present study has been planned to standardize the method of preparation of Yashada bhasma according to the method explained in the classical literature.